2017
DOI: 10.1016/j.cmet.2017.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiome-Based Metagenomic Signature for Non-invasive Detection of Advanced Fibrosis in Human Nonalcoholic Fatty Liver Disease

Abstract: SUMMARY The presence of advanced fibrosis in nonalcoholic fatty liver disease (NAFLD) is the most important predictor of liver mortality. There are limited data on the diagnostic accuracy of gut microbiota derived signature for predicting the presence of advanced fibrosis. In this prospective study, we characterized the gut microbiome compositions using whole-genome shotgun sequencing of DNA extracted from stool samples. This study included 86 uniquely well-characterized patients with biopsy-proven NAFLD, 72 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
837
3
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 855 publications
(903 citation statements)
references
References 46 publications
46
837
3
17
Order By: Relevance
“…utilized shotgun metagenomic sequencing, thus allowing for species level resolution, and noted that Bacteroides vulgatus and Escherichia coli were the most abundant species in patients with NAFLD-related advanced fibrosis. 17 This finding is concordant with a prior observation that Bacteroides vulgatus is a contributor to insulin resistance. 28 Due to utilization of 16S rRNA sequencing in other human studies examining advanced fibrosis, comparisons with these species-level findings are not feasible.…”
Section: Human Gut Microbiome Profiles In Clinical Phenotypes Of Naflsupporting
confidence: 91%
“…utilized shotgun metagenomic sequencing, thus allowing for species level resolution, and noted that Bacteroides vulgatus and Escherichia coli were the most abundant species in patients with NAFLD-related advanced fibrosis. 17 This finding is concordant with a prior observation that Bacteroides vulgatus is a contributor to insulin resistance. 28 Due to utilization of 16S rRNA sequencing in other human studies examining advanced fibrosis, comparisons with these species-level findings are not feasible.…”
Section: Human Gut Microbiome Profiles In Clinical Phenotypes Of Naflsupporting
confidence: 91%
“…Inosine and hypoxanthine (associated with nucleoside metabolism) are enriched in serum samples from patients with mild or moderate NAFLD (stage 0–2 fibrosis), whereas succinate, malate, α-ketoglutarate, glutamine, serine, fumarate, α-ketobutyrate, glutamate and lactate (associated with amino acid and carbon metabolism) are enriched in serum samples from patients with advanced fibrosis (stages 3–4) 44. A recent study also showed that severity of liver steatosis correlates with phenylacetic acid in humans 50.…”
Section: Metabolomic Studies Of Nafldmentioning
confidence: 99%
“…Clinical studies demonstrate that formate and acetate are enriched in faecal samples from adults with advanced fibrosis, whereas butyrate and propionate are enriched in faecal samples from adults with mild or moderate NAFLD 44. It therefore appears that levels and subtypes of SCFAs correlate with the severity of fatty liver disease.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 99%
“…They included 86 biopsy-proven NAFLD patietns (14 with stage 3 or 4 fibrosis). Using a metagenomic profile of 37 selected species along with age, BMI and diversity, they generated a model with an AUC of 0.936 to differentiate between early and advanced fibrosis in NAFLD 18 . The predicted metabolite functional change was not significant between groups but advanced fibrosis NAFLD patients had higher 3-phenylpropanoate, a product of anaerobic bacterial metabolism.…”
Section: Introductionmentioning
confidence: 99%